Politicization of Global Energy Supply: Historical and Contemporary Context - Yury V. Borovsky (Vestnik RUDN. International Relations)
The ongoing confrontation between Russia and the West over the conflict in Ukraine has revealed another, and unprecedented, example of the politicization of global energy supply. The politicization of energy supply represents an important phenomenon in international relations, which still lack a proper theoretical elaboration. This article aims to comprehensively examine and typologize the main manifestations of the politicization of global energy supply both in history and in modern international relations, with a special focus on the ‘energy confrontation’ between Russia and the West, provoked by the conflict in Ukraine. Theoretically, the research is based on the existing conceptual elaboration of the term ‘politicization,’ as well as on the vision of international relations by proponents of social constructivism and political realism. It relies on the methods of historical, system and comparative analysis, as well as the method of analogy. The author concludes that the politicization of energy supply is an integral attribute of international relations in the last half century. It can be hidden or open, moderate or extreme. The extreme form of politicization of energy supply, in contrast to the moderate one, involves the use of ‘energy weapons’ for political purposes, which equates it to an energy war. Energy wars can be limited or full-scale; unilateral, bilateral or multilateral. The conflict in Ukraine has provoked an open and extreme politicization of energy supply, which took the form of a full-scale, bilateral energy war after the start of Russia’s special military operation. The United States and its allies, seeking to influence the Russian policy towards Ukraine, have used ‘energy weapons’ to the fullest, and Russia has responded in kind, albeit on a limited scale.